KONSEP MUSYARAKAH MUTANAQISHAH DALAM HUKUM EKONOMI SYARIAH INDONESIA DAN MAJALLAT AL-AHKAM TURKI - febi, febi; Fahriansah, Fahriansah (IAIN Langsa, 2016)
Abstrak.This article is an attempt to compare between the Syariah Economic Law and the of Majallat al-Ahkam al-Adliya on the concept of Musyarakah mutanaqishah. The analisis is based on the assumption that both have different concept. It is found that the concept of Musyarakah mutanaqishah which the former referred to is more detail and systematic than the latter. However, the Majallat al-Ahkam has become the most important part for the development of the Islamic Economic Law in the world today. Kata Kunci: Musyarakah mutanaqishah, ekonomi syariah, majallat al-ahkam